Analisis Unsur Serapan dalam Kolom Opini Koran Kompas Edisi September 2023 - Sanjaya, M. Rama; Sanjaya, Muhammad Doni; Agustina, Aryanti (LPPM STKIP PGRI Bandar Lampung, 2024)
The purpose of this research is to analyze the borrowed elements in the opinion column of the Kompas newspaper, September 2023 edition. This research uses a descriptive type of research with a qualitative approach. The method used in this research is the descriptive method. Data collection in this research is through the utilization of documents. The researcher used qualitative descriptive data analysis techniques. Based on the analysis results, it can be concluded that there are 11 loanwords through the adoption process of English found in the opinion column of Kompas newspaper, September 2023 edition, 98 loanwords through the adoption process of Dutch found in the opinion column of Kompas newspaper, September 2023 edition, 37 loanwords through the adaptation process of English found in the opinion column of Kompas newspaper, September 2023 edition, and 18 loanwords through the adaptation process of Dutch found in the opinion column of Kompas newspaper, September 2023 edition. The borrowed words used in the opinion column of Harian Kompas September 2023 edition are already equivalent in meaning to those in the Indonesian Dictionary of Foreign Borrowed Words, Edition V. The absorption process in this study is categorized into two types, namely adoption and adaptation. Adoption is more commonly found compared to adaptation.